Os discursos da(e sobre) biblioteca: memórias e histórias; prazeres e serviços. - Feitosa, Glória Maria Carvalho de Alencastro (2015)
The proposed research aims to discuss the financing prospects of library space in the operative diversity of modernity. The research is qualitative, though , can provide quantitative data that will serve as input for data evaluation. The space for the generation of inferences of the research process will be the Central Library of the Federal University of Pernambuco, located in the city of Recife – PE. Contemporary thought seems to guide new " formats " to think the library , especially when it comes to meeting the needs of their immediate users ( students and teachers) and the general community. In this study will be pointed out the library missions, considered the historical background of its constitution and the current state , facing the requirements of postmodernity . The research will include performing data collection through an extensive review and consultation to official documents. We will be based on the theoretical considerations of Milanesi (2002) and Cunha (2010 ) . From the reference material can undertake analysis and identification ofproblems and, in such a case, we can mark out for the inset of discourse analysis, for than move to the guiding principle of systematic operation could be raised in the case of possible future action to be library, in addition to history and memory space also a place of inclusive services and pleasurable actions.